Sexual Abuse of Children and Young People by Catholic Priests and Religious: Description of the Problem from a Church Perspective - Scicluna, Charles J. (Sexual abuse in the catholic church. Scientific and legal perspectives. Proceedings of the conference "Abuse of children and young peole by catholic priests and religious" (Vatican City, April 2-5, 2003), 2004)
Proceedings of the conference "Abuse of children and young peole by catholic priests and religious" (Vatican City, April 2-5, 2003). Dieser Aufsatz beinhaltet eine Diskussion auf S. 23